Scaling up agricultural interventions: Case studies of climate-smart agriculture. (September 2018) - Westermann, Olaf; Förch, Wiebke; Thornton, Philip; Körner, Jana; Cramer, Laura; Campbell, Bruce
Abstract: If climate-smart agriculture (CSA) is meaningfully to address the development challenges posed by climate change, effective approaches will be needed to scale up research findings. Here, eleven case studies are used to exemplify scaling-up strategies based on (1) value chains and private sector involvement, (2) information and communication technologies and agro-advisory services, and (3) policy engagement. We evaluated these case studies and the scaling strategies they exemplify, using a simple conceptual framework from the field of scaling up nutrition interventions. Results showed that these different strategies exhibit different characteristics; all offer considerable potential for taking CSA interventions to scale, but there still may be unavoidable trade-offs to consider when choosing one strategy over another, particularly between reaching large numbers of farmers and addressing farmers' specific contexts. The case studies highlighted several challenges: estimating the costs and benefits of different scaling activities, integrating knowledge across multiple levels, and addressing equity issues in scaling up. The case studies outlined here will continue to be monitored and evaluated, thus strengthening the evidence base around effective scaling-up strategies that can contribute to achieving food and nutrition security under climate change in the coming decades. Highlights: Different strategies for scaling up climate smart interventions have different characteristics. Trade-offs may need to be made, including between reach and addressing local contexts. Robust information on the costs and benefits of scaling is lacking but difficult to generate. Scaling strategies may struggle to address equity concerns appropriately.